p-Mean Regret for Stochastic Bandits - Krishna, Anand; George John, Philips; Barik, Adarsh; Tan, Vincent Y. F. (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
In this work, we extend the concept of the p-mean welfare objective from social choice theory to study p-mean regret in stochastic multi-armed bandit problems. The p-mean regret, defined as the difference between the optimal mean among the arms and the p-mean of the expected rewards, offers a flexible framework for evaluating bandit algorithms, enabling algorithm designers to balance fairness and efficiency by adjusting the parameter p. Our framework encompasses both average cumulative regret and Nash regret as special cases. We introduce a simple, unified UCB-based algorithm (Explore-Then-UCB) that achieves novel p-mean regret bounds. Our algorithm consists of two phases: a carefully calibrated uniform exploration phase to initialize sample means, followed by the UCB1 algorithm of Auer et al. (2002). Under mild assumptions, we prove that our algorithm achieves a p-mean regret bound of Otilde( sqrt( k / T^1/(2|p|) ) ) for all p <= -1, where k represents the number of arms and T the time horizon. When -1< p < 0, we achieve a regret bound of Otilde( sqrt( k^1.5 / T^1/2 ) ). For the range 0 < p <= 1, we achieve a p-mean regret scaling as Otilde( sqrt( k / T ) ), which matches the previously established lower bound up to logarithmic factors. This result stems from the fact that the p-mean regret of any algorithm is at least its average cumulative regret for p <= 1. In the case of Nash regret (the limit as p approaches zero), our unified approach differs from prior work of Barman et al. (2023), which requires a new Nash Confidence Bound algorithm. Notably, we achieve the same regret bound up to constant factors using our more general method.